2019
DOI: 10.31231/osf.io/nfpsq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event-related Potential and Behavioural Differences in Affective Self-Referential Processing in Long-term Meditators versus Controls

Abstract: Contemplative practices are thought to modify one’s experience of self and fundamentally change self-referential processing. However, few studies have examined the effect of long-term meditation training on brain correlates of self-referential processing. Here we used the self-referential encoding task (SRET) to examine event-related potentials (ERP) during assessment of positive and negative self-views in long-term meditators versus demographically-matched meditation-naïve control participants. Compared to co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In particular, the N2 amplitude was calculated as the average amplitude at the electrode sites of F1, F2, and Fz between 300 and 400 ms after the onset of instructive cues (Clayson & Larson, 2013; Xue et al., 2013). The LPP amplitude was calculated as the average amplitude at the electrode sites of P3, P4, and Pz between 300 and 600 ms after cue onset (Katyal et al., 2020; Schienle et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the N2 amplitude was calculated as the average amplitude at the electrode sites of F1, F2, and Fz between 300 and 400 ms after the onset of instructive cues (Clayson & Larson, 2013; Xue et al., 2013). The LPP amplitude was calculated as the average amplitude at the electrode sites of P3, P4, and Pz between 300 and 600 ms after cue onset (Katyal et al., 2020; Schienle et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they reported no differences in long latency responses (LPP) (400–800 ms), corroborating with Sobolewski et al ( 2011 ) who studied Buddhist practices (CDM-OM), and reported LPP differences only in the frontal areas of the control group; and contrasting with Cosme and Wiens ( 2015 ) and Zhang et al ( 2019 ) who reported LPP differences between positive and negative pictures. Katyal et al ( 2020 ) explored a slightly different paradigm, the self-referential encoding task, which traditionally displays words related/unrelated to self, but here it was modified to employ self-related affective adjectives. They also reported LPP differences in the control group as opposed to Ananda Marga (NDM) meditators.…”
Section: Evoked Potentials/event Related Potentialsmentioning
confidence: 99%
“…Prior to the binocular rivalry study reported here, participants were administered a 6minute self-referential task, published elsewhere [23]. The present study involved the following sequence of blocks: 1) baseline audio, where participants kept their eyes closed and listened to a 524-second podcast, 2) five 80-sec runs of binocular rivalry (BR1), 3) 300 sec of chanting music for relaxation, 4) 1200-sec eyes-closed meditation, 5) five 80-sec runs of binocular rivalry (BR 2), 6) 900-sec eyes-closed meditation, and 7) five 80-sec runs of binocular rivalry (BR3).…”
Section: Methodsmentioning
confidence: 99%